The logic of suspense and the unthinkable in Sangama (1942) by Arturo Hernandez - Salas, Eduardo Avalos (2025)
Sangama (1942) by the author Arturo Hernández is one of the first novels of the thematic renewal of fiction about Amazonia. This article analyzes the novel from two points: first, the formal arrangement of the work will be studied from the narratology to demonstrate that this is not a merely descriptive novel as pointed out by literary critics. Thus, the novel would be arranged by what we have called «logic of narrative suspense» in which the narrative and discursive planes demonstrate an artificial plot that preserves the intrigue. Second, we will analyze Tula from postcolonial theory. We argue that she is an «unthinkable» subject, as Michel Trouillot has theorized, since she encourages suspense in the work and thus allows us to understand it. We argue that this novel proposes the opposite of what literary-critical studies have affirmed: Sangama is complex both in its form and in its characters, since in both cases it exceeds the traditional frameworks of representation.